2014
DOI: 10.1161/hypertensionaha.114.04067
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Cell-Type–Specific Responses to Angiotensin II Explain Cardiac Remodeling Differences in C57BL/6 Mouse Substrains

Abstract: T he highly used C57BL/6 mouse inbred strain is the preferred choice for mouse transgenic and knockout studies 1 and was the first strain whose genome was fully sequenced. 2 However, several C57BL6 substrains have emerged over the years, each showing genomic differences because of genetic drift and displaying various phenotypic differences. 1,3 One example is the difference between the C57BL/6J and C57BL/6N substrains. The C57BL/6 strain was initially developed at The Jackson Laboratory, and mice from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 39 publications
(28 reference statements)
1
18
1
Order By: Relevance
“…4A), suggesting that Nnt may play a protective role in a slowly-progressing aging heart. This is in contrast to observations that, with injury, the young B6N heart responds more severely to stress than age-matching B6J hearts [4, 37]. Although Nnt is considered an antioxidative enzyme, in pathophysiological conditions such as pressure overload (and perhaps in others) Nnt reverses its action and instead of generating NADPH, it depletes it to support NADH and ATP production.…”
Section: Discussioncontrasting
confidence: 62%
“…4A), suggesting that Nnt may play a protective role in a slowly-progressing aging heart. This is in contrast to observations that, with injury, the young B6N heart responds more severely to stress than age-matching B6J hearts [4, 37]. Although Nnt is considered an antioxidative enzyme, in pathophysiological conditions such as pressure overload (and perhaps in others) Nnt reverses its action and instead of generating NADPH, it depletes it to support NADH and ATP production.…”
Section: Discussioncontrasting
confidence: 62%
“…Although rodent strain selection has always been part of any study design, the increased availability and use of genetically modified rodents, particularly mice, as model systems for human diseases has revolutionized the way we conduct research in general while increasing awareness about the influence of genetic background on the resulting phenotype, which encompasses the cardiac phenotype. For example, many studies have reported mouse strain variations for cardiac function, 38,39 response to β-adrenergic stimulation 40 and angiotensin II, 41 and capacity for calcium handling, 42,43 but also for susceptibility to specific pathophysiological states, such as myocardial hypertrophy 44,45 or heart failure. 46 In terms of cardiac metabolism, only a few studies have made a systematic comparison among commonly used control mouse strains.…”
Section: General Methodological Considerationsmentioning
confidence: 99%
“…Surprisingly, research from the Maack Lab showed the NNT-null B6J mouse is protected from oxidative stress and heart failure in comparison with the B6N mouse, possibly because of a "reverse activity" of NNT in the B6N mouse (14). Furthermore, the NNT-replete B6N mice show increased fibrosis in response to chronic angiotensin II treatment, along with increased expression of cardiac remodelling genes; however, the authors demonstrate these changes are not due to NNT status (15). B6N mice are more susceptible to transaortic constriction than B6J with B6N having lower survival rates and cardiac function (17).…”
Section: Introductionmentioning
confidence: 92%
“…Subsequently, a further 19 families have been reported, with a single, highly consanguineous patient developing hypertrophic CM with a homozygous NNT mutation and three monoallelic variants have been linked to left ventricular non-compaction (10). A number of publications have linked NNT expression levels to cardiovascular traits, including remodelling differences, hypertension, and heart growth in mice and zebra fish (12,13,14,15,16). Surprisingly, research from the Maack Lab showed the NNT-null B6J mouse is protected from oxidative stress and heart failure in comparison with the B6N mouse, possibly because of a "reverse activity" of NNT in the B6N mouse (14).…”
Section: Introductionmentioning
confidence: 99%